Design of a Sintering Machine for 316L Material Products from 3D Printing for Product Design Engineering Laboratory - Adi S Pradipta; Dinny Indrian (Jurnal Teknik Mesin Mechanical Xplore, 2025)
The increasing demand for high-performance metal components in additive manufacturing necessitates effective post-processing methods to enhance material density and mechanical properties. This study presents the design of a compact laboratory-scale sintering machine for 316 L stainless steel components fabricated using fused-filament fabrication (FFF). The design process adopted a simplified VDI 2222 methodology encompassing planning, conceptual design, and detailed design stages. Functional decomposition and systematic evaluation of the alternative design concepts were conducted using the VDI 2225-based assessment method, leading to the selection of the optimal configuration. Thermal analysis and radiation-based simulations demonstrated that the proposed system is capable of achieving the required sintering temperature range for 316 L stainless steel (approximately 1100–1300 °C) with a stable heat distribution. Structural analysis further confirmed that all critical components operated within acceptable safety limits, with safety factors exceeding the standard design criteria. Overall, the proposed design provides a technically feasible and safe solution for laboratory-scale sintering, supporting research and prototyping in metal additive manufacturing.